Hydrogen permeation of X80 steel with superficial stress in the presence of sulfate-reducing bacteria. (February 2015) - Wu, Tangqing; Yan, Maocheng; Zeng, Dechun; Xu, Jin; Sun, Cheng; Yu, Changkun; Ke, Wei
Highlights: We studied the effects of CP, SRB and superficial stresses on hydrogen permeation. The superficial stresses and cathodic potential enhance hydrogen permeation. SRB has a positive role in hydrogen permeation at cathodic protection. SRB and superficial stresses have synergistic effects on promoting permeation. Abstract: In this paper, investigations on hydrogen permeation of X80 pipeline were conducted under superficial stress and cathodic protection in the presence of sulfate-reducing bacteria (SRB). Superficial stress was introduced to X80 pipeline steel by mechanical abrading. The mechanical abrading process trends to increase the surface area ratio and introduce compression stresses on the steel surface. The activity of SRB, the superficial stress and the cathodic potentials accelerate the hydrogen flux of the steel in the soil solution. SRB and superficial stresses have synergistic effects on promoting hydrogen flux of the steel in the soil solution.